Zinc inhibits lethal inflammatory shock by preventing microbe‐induced interferon signature in intestinal epithelium - Jolien Souffriau; Steven Timmermans; Tineke Vanderhaeghen; Charlotte Wallaeys; Kelly Van Looveren; Lindsy Aelbrecht; Sylviane Dewaele; Jolien Vandewalle; Evy Goossens; Serge Verbanck; Filip Boyen; Melanie Eggermont; et al. (EMBO Molecular Medicine)
Abstract The cytokine TNF drives inflammatory diseases, e.g., Crohn's disease. In a mouse model of TNF‐induced systemic inflammatory response syndrome (SIRS), severe impact on intestinal epithelial cells (IECs) is observed. Zinc confers complete protection in this model. We found that zinc no longer protects in animals which lack glucocorticoids (GCs), or express mutant versions of their receptor GR in IECs, nor in mice which lack gut microbiota. RNA‐seq studies in IECs showed that zinc caused reduction in expression of constitutive (STAT1‐induced) interferon‐stimulated response (ISRE) genes and interferon regulatory factor (IRF) genes. Since some of these genes are involved in TNF‐induced cell death in intestinal crypt Paneth cells, and since zinc has direct effects on the composition of the gut microbiota (such as several Staphylococcus species) and on TNF‐induced Paneth cell death, we postulate a new zinc‐related anti‐inflammatory mechanism. Zinc modulates the gut microbiota, causing less induction of ISRE/IRF genes in crypt cells, less TNF‐induced necroptosis in Paneth cells, and less fatal evasion of gut bacteria into the system.